Upaya Penurunan Nilai COD Pada Limbah Tekstil Dan Batik Dengan Penambahan NaOCl - Linda Aliffia Yoshi; Jessica Ambarwati Idat; Galuh Maulidyananda; Ratnawati (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2020)
Batik and textile production produces liquid waste with a COD content above the environmental quality standard between 2,000-12,000 ppm. Efforts to reduce the value of COD are helped by the addition of NaOCl. This study aims to determine the pH and dose of NaOCl against COD reduction. Textile liquid waste used came from factory X while batik liquid waste came from factory Y; both factories are located in South Tangerang. In this study, the pH range, 5, 7, and 9 and NaOCl concentrations were added in 3000, 4000, and 5000 ppm. The study begins with the measurement of the actual COD value in the two wastewater. The best results for batik waste were obtained at pH 5 with the addition of 4000 ppm NaOCl which resulted in a decrease of 93%. Textile liquid waste shows the best results at pH 5 with an additional 5000 ppm NaOCl concentration which can reduce COD by 95%. The final result of the COD value has met the quality standard set by the government which is less than 250 ppm.